Characterization of genetic subclonal evolution in pancreatic cancer mouse models - Noushin Niknafs (Nature Portfolio, 2019)
In pancreatic cancer the Kras and Trp53 transgene driven KPC mouse model is used to experimentally study disease processes. Here, the authors analyse tumour evolution within the KPC model, finding both linear and branched evolution and highlighting the utility of this model in mechanistic research of tumour evolution.